FUNGSI BADAN PERMUSYAWARATAN DESA DALAM MENAMPUNG DAN MENYALURKAN ASPIRASI MASYARAKAT DESA - Pala, Adelbertus Yosep; Purwatiningsih, Annisa; Arvianti, Eri Yusnita (Jurnal Ilmiah Publika, 2023)
The Village Consultative Board, hereinafter referred to as the BPD, is an institution that is the embodiment of democracy in the administration of village governance. In accordance with Law No. 6/2014 on Villages, the Village Consultative Board functions as a board that discusses and agrees on draft village regulations with the Village Head, as well as accommodates and channels the aspirations of the village community, and supervises the performance of the Village Head. This research used qualitative methods using data collection techniques through interviews, observation and documentation. The sampling was through the purposive sampling. To test the validity of the data, the researchers used trangulation techniques. In the regulation of the Minister of Home Affairs of the Republic of Indonesia No. 110 of 2016 on the village consultative board item a, b, and d, has a task, namely to explore the aspirations of the community, to absorb the aspirations of the community, and to channel the aspirations of the community. Therefore, in order to absorb the aspirations of the community, the Tlekung Village Consultative Board must be closer to the community as the development in the village itself comes from the aspirations of the community. Eventually, it can be channeled to the village government to create programs that can solve existing problems. Based on the results of the study, it shows that the function of Tlekung Village Consultative Board in carrying out the task of exploring, accommodating and channeling the aspirations of the village community is going well. The supporting factors in this study are the harmonious relationship between the Village Consultative Board and the Village Government, so that the Village Consultative Board is facilitated by the Village Government in carrying out its activities, and the enthusiastic participation of the community in communicating their aspirations. Meanwhile, the inhibiting factor is the difference of views in the meeting between the Village Consultative Board and the Village Government. However, this is considered normal to achieve consensus so that the discussion of the Village Mid-Term Village Development Plan (RPJMDes), which is outlined in the annual Village Government Work Plan (RKP), runs well.